2022
DOI: 10.1097/phh.0000000000001613
|View full text |Cite
|
Sign up to set email alerts
|

Grouping Public Health Skills to Facilitate Workforce Development: A Factor Analysis of PH WINS

Abstract: Objectives: This study examined whether distinct factors exist among public health skills, measured through the Public Health Workforce Interests and Needs Survey (PH WINS). Understanding how workforce training needs group is important for developing targeted and appropriate public health workforce training sessions. Design: Exploratory factor analysis was used to examine public health skills among tier 1 staff (nonmanagers) and a combined group of tier 2 and 3 staff (managers and executives). Setting: Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In a study using 2017 Public Health Workforce Interests and Needs Survey (PH WINS) data representing only mid- and large-sized LHDs, “significant data and informatics skill gaps” were identified among the “broader public health workforce.”16 While few studies of public health data capacity specific to rural public agencies exist,1 one could presume that the 2017 PH WINS findings would have been more “significant” for rural agencies, had the 2017 PH WINS included small or rural agencies. Another study, conducting a factor analysis using 2017 PH WINS data, found “communication skills and data use skills loading onto the same factor,” suggesting that public health practice capacities regarding communication and data skills relate closely to one another 17. Our respondents similarly described a combined lack of capacity regarding understanding and communicating with data that hampered their efforts.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In a study using 2017 Public Health Workforce Interests and Needs Survey (PH WINS) data representing only mid- and large-sized LHDs, “significant data and informatics skill gaps” were identified among the “broader public health workforce.”16 While few studies of public health data capacity specific to rural public agencies exist,1 one could presume that the 2017 PH WINS findings would have been more “significant” for rural agencies, had the 2017 PH WINS included small or rural agencies. Another study, conducting a factor analysis using 2017 PH WINS data, found “communication skills and data use skills loading onto the same factor,” suggesting that public health practice capacities regarding communication and data skills relate closely to one another 17. Our respondents similarly described a combined lack of capacity regarding understanding and communicating with data that hampered their efforts.…”
Section: Discussionmentioning
confidence: 67%
“…Another study, conducting a factor analysis using 2017 PH WINS data, found "communication skills and data use skills loading onto the same factor," suggesting that public health practice capacities regarding communication and data skills relate closely to one another. 17 Our respondents similarly described a combined lack of capacity regarding understanding and communicating with data that hampered their efforts.…”
Section: Discussionmentioning
confidence: 95%
“…We used an exploratory factor analysis approach to determine underlying latent structures present in public health workforce skills among three staff tiers: nonmanagers, managers and supervisors, and executive‐level staff (Petrovskis et al, 2022b). We aimed to better understand how various public health skills grouped together, including what skills grouped with data use skills.…”
Section: Methodsmentioning
confidence: 99%
“…From this preliminary model, we identified specific gaps and narrowed our final model to include only individual and organizational-level factors (Figure 2). We then conducted two quantitative analyses that were a factor analysis of public health skills and a multivariate linear regression analysis to empirically test elements of our proposed theoretical model and refine relationships in our final model (Petrovskis et al, 2022a(Petrovskis et al, , 2022b. Lastly, we incorporated evaluation findings from a training series for public health practitioners that was focused on data use and health disparities knowledge attainment to further support relationships between certain concepts in our model Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation